Corporate Governance in South Korean Laws: Some Suggestions for Vietnam - Thuy, Phan (VNU Journal of Science: Legal Studies; Vol 36 No 2DO - 10.25073/2588-1167/vnuls.4302, 2020)
Having an advanced legal framework for corporate governance is always one of the most prerequisites for effective business operation of joint stock companies. Being aware of this issue, since the first enactment in 1990, enterprise law in Vietnam has been consecutively improved and newly promulgated to absorb the OECD modern principles of corporate governance and good international practices, particularly from the developed countries which have successful economic cooperation with Vietnam in Asia. This article will focus on exploring and analyzing and making comments on the legal framework and corporate structures of joint stock company regulated in Korean Commercial Code. In term of comparison with those similar elements in Vietnamese Enterprise Law 2014, the article will also make recommendations as suggestions for the improvement of corporate governance law in the country. Keywords: joint stock company, corporate governance, corporate structures, general meeting of shareholders, board of directors, independent directors. References: [1] Park JD, Korea’s Path of Development in Retrospect, trong sách Re-Inventing Africa's Development. Palgrave Macmillan, Cham 2019, (tr.180-201). [2] Jin Oh Seung, Overview of Legal Systems in the Asia-Pacific Region: South Korea, trong Overview of Legal Systems in the Asia- Pacific Region (2004). Paper 6 tại: http://scholarship.law.cornell.edu/lps_lsapr/6. (truy cập 22/2/2019) [3] Black's Law Dictionary (10th Edition), in Co, Bryan A. Garner (Chief Editor), Editor. 2014,, Thomson Reuters, tr. 312. [4] Commercial Act of Korea tại: http://law.go.kr/lsInfoP.do?lsiSeq=176698&urlMode=engLsInfoR&viewCls=engLsInfoR#0000 (truy cập 5/12/2019). [5] Commercial Act of Korea, tlđd. [6] Stock Company tại http://koreanlii.or.kr/w/index.php/Company?ckattempt=1 ( truy cập 23/2/2020). [7] Phan Thị Thanh Thủy, Bàn về tính minh bạch trong quản trị công ty cổ phần ở Việt Nam, Nghiên cứu Lập pháp, kỳ 1 tháng 1/2018, 53-55. [8] Corporate Governance in Korea, International Financial Law Review, tại: https://www.iflr.com/Article/2027067/Corporate-governance-in-Korea.html (truy cập 22/12/2019). [9] LDN 2014 gọi là trách nhiệm của người quản lý công ty cổ phần quy định tại Khoản 1 Điều 160. [10] Lucian a. Bebchuk & Assaf Hamdan, Independent directors and controlling shareholders, University of Pennsylvania Law Review, 2016. Vol. 165,(6): p.1271-1280. [11] Chun, K.H., Korea's Mandatory Independent Directors: Expected and Unexpected Roles, tại https://ssrn.com/abstract=2824303 P9-10 (truy cập 22/1/2020). August 2016,. [12] Block, D.a.G., Anne-Marie, One-Tier vs. Two-Tier Board Structure: A Comparison Between the United States and Germany, Comparative Corporate Governance and Financial Regulation. https://scholarship.law.upenn.edu/fisch_2016/1 2016, p.6 (truy cập 22/2/2020). [13] https://www.tmf-group.com/en/news-insights/articles/2019/february/external-audit-act/. [14] OECD, Nguyên tắc Đối xử bình đẳng giữa các cổ đông trong sách Các nguyên tắc quản trị công ty của OECD tại: https://www.oecd.org/daf/ca/corporategovernanceprinciples/45034702.pdf, tr. 41-47;. 2004. [15] Phan Thị Thanh Thủy, Chương 6, Pháp luật điều chỉnh hành vi kinh doanh ở Việt Nam , tr 251 – 257, trong sách Thể chế pháp luật kinh doanh Việt Nam trong bối cảnh hội nhập cộng đồng kinh tế ASEAN, Phan Thị Thanh Thủy, Chủ biên, NXB Đại học Quốc gia, 2019. [16] Dự thảo Luật Doanh nghiệp (sửa đổi) tháng 3/2020 tại http://duthaoonline.quochoi.vn/DuThao/Lists/DT_DUTHAO_LUAT/View_Detail.aspx?ItemID=1773&LanID=1811&TabIndex=1 (24/3/2020).